Calculating a statistically robust δ13C and δ15N offset for charred cereal and pulse seeds - Nitsch, E; Charles, M; Bogaard, A (Maney Publishing, 2015)
This study measured δ13C and δ15N of fresh and charred seeds from six different taxa of cereals and pulses. For each taxon, 12 different batches of seeds, all from the same growing context or field, were charred for 4, 8, or 24 hours at 215, 230, 245, or 260°C, with the thirteenth batch left uncharred. The least charred samples showed no average offset compared to their uncharred counterparts, but among the charred seeds, every 15°C increase resulted in an increase in δ15N by 0.12‰, while increasing the duration of charring by 4 hours resulted in an average increase of 0.04‰. Differences in δ13C among the charred samples were only minimally dependent on time (+0.016‰/4 hours duration), but not temperature. The average offset for all batches and all taxa was minimal for δ13C, at +0.11‰ (95% confidence interval (CI) 0.003–0.22‰). The average offset for δ15N of 0.31‰ (95% CI 0.05–0.57‰) is smaller than the conservative estimate of 1‰ used in previous studies. We demonstrate that using this new, smaller charring offset for δ15N makes a significant difference in paleodietary models, one that further emphasizes the potentially high δ15N of manured crops relative to animal forage.